HUBUNGAN PENYEBAB HIPERTENSI TERHADAP KEJADIAN HIPERTENSI DI PUSKESMAS PASANEA KECAMATAN SERAM UTARA BARAT - Siti Nurhidayati; Nova Bugis; Ezra M Siahaya (STIKES Pasapua Ambon, 2021)
Introduction: Changes in lifestyle and diet have consequences for the development of degenerative diseases, including hypertension. At the Pasanea Health Center in the last three years there were 67 people with hypertension. The aim of this study was to determine the relationship between the causes of hypertension and the incidence of hypertension at the Pasanea Health Center, Kec. North West Seram. Method: The research method used is descriptive analytic method with a cross sectional approach. The population is all hypertension sufferers totaling 67 people in the working area of the Pasanea Health Center, North West Seram District. The sample was taken using the total sampling technique. There were 67 samples in this study. Results: The results showed that there was a relationship between consumption of salt intake and hypertension (p = 0.000), there was a relationship between consumption of fatty foods and hypertension (p = 0.000), there was no relationship between physical activity and hypertension (p = 0.000). 0.260). Conclusion: there is a relationship between consumption of salt intake and hypertension at the Pasane Health Center, there is a relationship between consumption of fatty foods and hypertension at the Pasane Health Center and there is no relationship between physical activity and hypertension at the Pasane Health Center.